Real-time polymerase chain reaction detection and surgical treatment of thoracic and lumbar spondylitis due to Brucella infection: two typical case reports - Liu, Bo; Ji, Yun-xiao; Zhao, Chang-song; Zhang, Qiang (Frontiers in Public Health, 2024)
Background Spondylitis caused by Brucella infection is a rare but challenging condition, and its successful management depends on timely diagnosis and appropriate treatment. This study reports two typical cases of thoracic and lumbar brucellosis spondylitis, highlighting the pivotal roles of real-time polymerase chain reaction (real-time PCR) detection and surgical intervention. Case presentation Case 1 involved a 49-year-old male shepherd who presented with a 6-month history of fever (40°C), severe chest and back pain, and 2-week limited lower limb movement with night-time exacerbation. Physical examination revealed tenderness and percussion pain over the T9 and T10 spinous processes, with grade 2 muscle strength in the lower limbs. CT showed bone destruction of the T9 and T10 vertebrae with narrowing of the intervertebral space, whereas MRI demonstrated abnormal signals in the T9–T10 vertebrae, a spinal canal abscess, and spinal cord compression. The Rose Bengal plate agglutination test was positive. Case 2 was a 59-year-old man who complained of severe thoracolumbar back pain with fever (39.0°C) and limited walking for 2 months. He had a 2.5 kg weight loss and a history of close contact with sheep. The Rose Bengal test was positive, and the MRI showed inflammatory changes in the L1 and L2 vertebrae. Diagnosis and treatment: real-time PCR confirmed Brucella infection in both cases. Preoperative antimicrobial therapy with doxycycline, rifampicin, and ceftazidime-sulbactam was administered for at least 2 weeks. Surgical management involved intervertebral foraminotomy-assisted debridement, decompression, internal fixation, and bone grafting under general anesthesia. Postoperative histopathological examination with HE and Gram staining further substantiated the diagnosis. Outcomes: both patients experienced significant pain relief and restored normal lower limb movement at the last follow-up (4–12 weeks) after the intervention. Conclusion Real-time PCR detection offers valuable diagnostic insights for suspected cases of brucellosis spondylitis. Surgical treatment helps in infection control, decompression of the spinal cord, and restoration of stability, constituting a necessary and effective therapeutic approach. Prompt diagnosis and comprehensive management are crucial for favorable outcomes in such cases.